Perencanaan Kebutuhan Bahan Baku Keramik BHL244S dan HM-2 dengan Metode Material Requirement Planning - Ayudina Puji Estrimaz; Rudy Hendrawanto (Jurnal Teknik Industri, 2001)
PT. Kuda Laut Mass is a private company which produce floor tile. The problem that usually happen in this company is how to make planning in material requirement especially count the quantity of material and component and also release that will ber educe the production cost.